COMPREHENSIVE ASSESSMENT OF THE LEVEL OF EMOTIONAL AND PERSONAL WELL-BEING OF LECTURERS OF A TECHNICAL UNIVERSITY: SUMMATIVE ASSESSMENT - Elena V. Rodionova; Tatiana V. Konyukhova (Векторы благополучия: экономика и социум, 2022)
Positive emotional background is reflected in a person's sense of well-being. In assessing the emotions and feelings experienced by a person, well-being acts as a personal disposition, characterized by satisfaction, a state of happiness, a sense of personal integrity, internal balance and harmony. In foreign studies, subjective and psychological well-being are considered as separate constructs, while in domestic studies, a clear distinction is not made. Foreign and domestic models of well-being and the scale of its measurement are considered. The integrating definition of the hedonistic and eudemonistic approaches is «emotional and personal well-being», where the personal component is close to psychological, and the emotional component is close to subjective well-being. Of particular importance is the awareness and feeling of one's own well-being for lecturers, who are constantly faced with the need for active restructuring, growing demands. In addition, lecturers personify the frontiers between education and science, present and future. This imposes a huge responsibility. Many university staff regularly experience stressful experiences, emotional exhaustion and, as a rule, a decrease in the level of psychological well-being. The purpose of the study, conducted in January 2022, is a comprehensive assessment of the level of emotional and personal well-being of lecturers, which affects the quality of their professional activities, mastering the necessary competencies and the stress resistance of the indivi-dual. The sample consisted of 61 respondents from among the teaching staff of a technical university. Based on the results of processing the data array, it was shown that the subjects have a more pronounced emotional aspect, which correlates with subjective well-being. A highly significant statistically positive relationship between the level of «emotional and personal well-being» and the level of emotional intelligence was revealed (r=0,471, p≤0,01). This allowed us to conclude that the higher the level of emotional intelligence of lecturers, the higher the «emotional and personal well-being», satisfaction with oneself, one's own life, positive perception of the world around, and other indicators. The authors have identified risk groups in need of purposeful optimization of the emotional and personal sphere.